2013
DOI: 10.1016/j.exer.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceria inhibit expression of genes associated with inflammation and angiogenesis in the retina of Vldlr null mice

Abstract: Oxidative stress and inflammation are important pathological mechanisms in many neurodegenerative diseases, including age-related macular degeneration (AMD). The Very Low-Density Lipoprotein Receptor knockout mouse (Vldlr−/−) has been identified as a model for AMD and in particular for Retinal Angiomatous Proliferation (RAP). In this study we examined the effect of cerium oxide nanoparticles (nanoceria) that have been shown to have catalytic antioxidant activity, on expression of 88 major cytokines in the reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 72 publications
(100 reference statements)
7
55
0
Order By: Relevance
“…4 A(i,ii)). These data are consistent with the previous work of Cai et al [30], and Kyosseva and co-workers [28] who also demonstrated that the administration of nanoceria was associated with decreased evidence of cellular inflammation and the attenuation of MAPK phosphorylation. To extend these findings we next examined if the nanoparticle treatment was also able to protect the liver from sepsis-induced apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 A(i,ii)). These data are consistent with the previous work of Cai et al [30], and Kyosseva and co-workers [28] who also demonstrated that the administration of nanoceria was associated with decreased evidence of cellular inflammation and the attenuation of MAPK phosphorylation. To extend these findings we next examined if the nanoparticle treatment was also able to protect the liver from sepsis-induced apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…2 and Selvaraj et al Table 3 [16]). These latter data are in agreement with the previous work of Kyosseva and colleagues who demonstrated that a single injection of nanoceria in the neurodegeneration prone Vldlr–/– mouse was able to attenuate the expression of several proinflammatory cytokines and proangiogenic growth factors [28]. …”
Section: Discussionsupporting
confidence: 92%
“…3, HL-217 decreased the expression of proangiogenic factors (osteopontin, heparin-binding epidermal growth factor-like growth factor (HB-EGF), leptin, PDGF-AB/BB, tissue factor (TF), insulin-like growth factor binding protein-2 (IGFBP-2), CXC chemokine ligand 16 (CXCL16), IGFBP-3, fibroblast growth factor-1 (FGF-1), IGFBP-3 and matrix metalloproteinase-9 (MMP-9)) in Vldlr À/À mice compared with vehicle treatment. Consistent with a previous report [19], pro-angiogenic growth factors such as leptin and FGF-1 were up-regulated in vehicle-treated Vldlr À/À mice. By contrast, anti-angiogenic factors such as endostatin and platelet factor-4 (PF-4) were down-regulated by HL-217.…”
Section: Hl-217 Regulates the Expression Of Angiogenesis-associated Fsupporting
confidence: 91%
“…Here the expression of CD31; which is one most widely used endothelial cell marker for studying angiogenesis and neovascularization; was significantly reduced (up to 60%) in tumors of CNP treated mice compared to the control group [43]. In addition; an anti-angiogenic effect of CNP was described for ovarian cancer and agerelated macular degeneration by other research groups as well [76,77]; but to our knowledge nothing was described for glioma-endothelial cell interactions so far. As CNP impede migration; invasion and tube formation of ECs; our findings suggest an inhibition or decrease of the release of soluble (pro-invasive) factors by the studied cells.…”
Section: Discussionmentioning
confidence: 96%